2014
DOI: 10.21273/hortsci.49.6.785
|View full text |Cite
|
Sign up to set email alerts
|

Essential Oil Yield and Composition of Garden Sage as a Function of Different Steam Distillation Times

Abstract: Garden sage (Salvia officinalis L.) is a medicinal, culinary, ornamental, and essential oil plant with a wide range of ecological adaptation. Garden sage essential oil traditionally is extracted by steam distillation from the above-ground biomass and has widespread applications as an aromatic agent in the food and pharmaceutical industries as well as in perfumery and cosmetics. The hypothesis of this study was that the steam distillation time (DT) may significantly affect ess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…This is consistent with some literature data reporting a 25-40% decrease in yield for some Cymbopogon EOs with increasing time [23]. Numerous studies have confirmed that EO yield decreases with time [24][25][26] or at least reaches equilibrium at some point without further increase [27][28][29]. There are also data from the literature suggesting different effects of drying on EO content [30], as some studies noted a significant decrease in yield [31], while others reported an increase [26].…”
Section: Eo Extractionsupporting
confidence: 90%
“…This is consistent with some literature data reporting a 25-40% decrease in yield for some Cymbopogon EOs with increasing time [23]. Numerous studies have confirmed that EO yield decreases with time [24][25][26] or at least reaches equilibrium at some point without further increase [27][28][29]. There are also data from the literature suggesting different effects of drying on EO content [30], as some studies noted a significant decrease in yield [31], while others reported an increase [26].…”
Section: Eo Extractionsupporting
confidence: 90%
“…Thus, the study conducted by Rosa et al [ 32 ], as well as the results obtained in our work, demonstrate the importance of proposing new methodologies for the optimization of the steam distillation process, especially from an industrial point of view. In addition, because experiments are widely performed at the laboratory scale, it was noted that most of the articles involving the analysis of the EO extraction yield for lemongrass and another vegetal sources are presented as % [ 33 35 ]. This mode of presentation was found in the work performed by Boukhatem et al [ 36 ], which reported a yield of 0.6% after 15 minutes of extraction when attempting to obtain EO from lemongrass by means of the solvent-free microwave extraction technique.…”
Section: Resultsmentioning
confidence: 99%
“…The outcome is noteworthy, and the result can be used to maximize the recovery of essential oil of V. jatamansi. The effects of duration of distillation time on recovery of essential oil have been reported in many aromatic plants [38,39,41,44,[52][53][54][55][56].…”
Section: Discussionmentioning
confidence: 99%